Impacts of COVID-19 on the Income and Mental Well-Being of Cismen, Ciswomen, Transgender, and Non-Binary Individuals : Evidence from the 2020 COVID-19 Disparities Survey - Ahmed, Tanima; Lebbos, Toni Joe; Howell, Sean; Lamontagne, Erik; Wimpey, Joshua Seth (World Bank, Washington, DC, 2022)
This paper uses the first round of the 2020 COVID-19 Disparities Survey to examine the impacts of the COVID-19 pandemic on the income and mental well-being of cismen, ciswomen, transgender, and non-binary individuals. The analysis shows that the pandemic led to high job and income loss expectations among transgender and non-binary individuals. The pandemic has also led to a disproportionate reported decrease in consumption for transgender and non-binary people compared to cismen, potentially related to a high rate of anxiety, loneliness, and depression observed in the group. The results highlight that the disproportionate economic impacts resulting from the COVID-19 pandemic might cause further declines in the economic conditions of transgender and non-binary people, thus exacerbating existing vulnerabilities in the community.